2013
DOI: 10.5812/nms.8555
|View full text |Cite
|
Sign up to set email alerts
|

Medication Management Skills of Nursing Students: Comparing the Students and Their Instructors` Evaluation in two Universities

Abstract: Background: Nurses have critical roles in the process of medication. Evaluating the process of medication helps nursing educators and students to determine the present status and then, improve the quality of care. Objective: The current study was conducted to compare the self-evaluation of nursing students in their own medication skills with the evaluation done by clinical instructors, in Qom's Azad University and Arak University of Medical Sciences, in 2011. Materials and Methods: A descriptive study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Another study identified that the nursing students are not competent in the process of medication therapy both from their own and their clinical instructor's perspectives that calls an urgent need to take actions to strengthen the students' skills in medication administration and dosage calculation (Zare, Purfarzad, & Adib-Hajbaghery, 2013 Westbrook, et al, 2011;Zare, et al, 2013) and threat to patient safety (Cheragi, et al, 2013;David, et al, 2013;Fleming, et al, 2014). A recent study identified lacking in nursing curricula that should develop the nurse's competence in pharmacology and drug dosage calculation during the basic nursing training.…”
Section: Nurses Training Need For Drug Dosage Calculationmentioning
confidence: 99%
“…Another study identified that the nursing students are not competent in the process of medication therapy both from their own and their clinical instructor's perspectives that calls an urgent need to take actions to strengthen the students' skills in medication administration and dosage calculation (Zare, Purfarzad, & Adib-Hajbaghery, 2013 Westbrook, et al, 2011;Zare, et al, 2013) and threat to patient safety (Cheragi, et al, 2013;David, et al, 2013;Fleming, et al, 2014). A recent study identified lacking in nursing curricula that should develop the nurse's competence in pharmacology and drug dosage calculation during the basic nursing training.…”
Section: Nurses Training Need For Drug Dosage Calculationmentioning
confidence: 99%
“…Another study identified that the nursing students are not competent in the process of medication therapy both from their own and their clinical instructor's perspectives that calls an urgent need to take actions to strengthen the students' skills in medication administration and dosage calculation (Zare, Purfarzad, & Adib-Hajbaghery, 2013 (Cheragi, et al, 2013;David, et al, 2013;Fleming, et al, 2014). A recent study identified lacking in nursing curricula that should develop the nurse's competence in pharmacology and drug dosage calculation during the basic nursing training.…”
Section: Nurses Training Need For Drug Dosage Calculationmentioning
confidence: 99%
“…Various studies have concluded that nursing students are not prepared for real practical work and current educational programs are insufficient [41]. They feel unprepared with the responsibility of their professional role [42,43].…”
Section: Introductionmentioning
confidence: 99%